Assessment of Pulmonary Function After Treatment of Scoliosis: Meta-Analysis and Review Article - Majdi Hashem (Medicina)
Background and Objectives: Pulmonary function is a key outcome in scoliosis management, as both the condition and its treatments can impact respiratory mechanics. This systematic review aimed to assess the effects of scoliosis interventions on pulmonary function, focusing on forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and peak expiratory flow (PEF). Materials and Methods: A comprehensive literature search was conducted in PubMed, Web of Science, Scopus, and the Cochrane Library to identify studies evaluating pulmonary function before and after scoliosis treatment. Data on respiratory parameters, intervention types, and follow-up periods were extracted. Meta-analyses were performed using standardized mean differences (SMDs) with 95% confidence intervals (CIs). Heterogeneity was assessed using the I2 statistic. Results: The meta-analysis revealed no significant overall effect of scoliosis interventions on FVC or FEV1. For FVC, the pooled effect size was 0.0126 (95% CI: −0.0161 to 0.0413; p = 0.3728), and for FEV1, it was 0.0034 (95% CI: −0.0452 to 0.0519; p = 0.8869). Heterogeneity was minimal (I2 = 0.0%) for both metrics. Individual studies showed variability: some reported increases in FVC and FEV1 by over 1.5 L, while others observed decreases in percent predicted values and absolute volumes. PEF generally improved, with some interventions showing statistically significant gains (p < 0.001). Conclusions: Non-invasive rehabilitation methods, such as breathing exercises and aquatic therapy, were associated with more consistent improvements in pulmonary function. In contrast, the effects of surgical interventions were variable and often not statistically significant. These findings suggest a promising role for conservative therapies in enhancing long-term respiratory outcomes in scoliosis patients, though further high-quality research is warranted.